2015
DOI: 10.1097/jac.0000000000000085
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the Effectiveness of State-Level Community Health Worker Initiatives Through Ambulatory Care Partnerships

Abstract: The transformation of the US health care system and the recognition of the effectiveness of community health workers (CHWs) have accelerated national, state, and local efforts to engage CHWs in the support of vulnerable populations. Much can be learned about how to successfully integrate CHWs into health care teams, how to maximize their impact on chronic disease self-management, and how to strengthen their role as emissaries between clinical services and community resources; we share examples of effective str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Strategies to identify and address social determinants of health, which contribute to adverse outcomes among marginalized patient populations, should be explored 33 . For example, the addition of community health workers to the multidisciplinary team has been shown to be a cost‐effective, strategy to improve diabetes control in vulnerable populations 34,35 . Programs which target the development of a diverse clinical workforce that mirrors the nation's demographics may improve clinician‐patient relationships and lead to enhanced patient engagement 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Strategies to identify and address social determinants of health, which contribute to adverse outcomes among marginalized patient populations, should be explored 33 . For example, the addition of community health workers to the multidisciplinary team has been shown to be a cost‐effective, strategy to improve diabetes control in vulnerable populations 34,35 . Programs which target the development of a diverse clinical workforce that mirrors the nation's demographics may improve clinician‐patient relationships and lead to enhanced patient engagement 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent case studies and reviews of implementation science literature have suggested that a potential barrier to success for new CHW programs can be inadequate connections to clinicians/health care delivery and poorly defined roles. [60][61][62] Future efforts in sustaining this program and others in interventional audiology will rely on expanding training opportunities, interprofessional collaboration, and identifying mechanisms for financial support.…”
Section: Discussionmentioning
confidence: 99%
“…62,63 Home visits may extend the clinic's reach, but require new strategies for remote supervision and technology access. 64,65 Decisions about how to best utilize CHW-PCs depend on needs of patients and care teams, clinical workflows, financial viability, and addressing practice burdens while facilitating performance 66,67 and cost-savings. 68 Increasing the presence of CHW-PCs also requires training and clinical integration necessary to build this new workforce, 59,69 including certification, 58 health information technology, and clinical oversight for the breadth of contributions CHW-PCs offer.…”
Section: Provides Limited Medication Reconciliation Without Making Rementioning
confidence: 99%